(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article describes the historical basis of using the scientific heritage of ancestors in the correct use of geographical object and place names. In particular, in the study of the scientific heritage of Mahmud Koshgari, special attention is paid to folklore studies and scientific popular works, to studies in the fields of oriental studies and geography.